2019
DOI: 10.1590/1678-5150-pvb-5520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eCG on the follicular dynamics and vascularization of crossbred cows with different circulating progesterone concentrations during synchronization of ovulation in an FTAI protocol

Abstract: This study aimed to evaluate the effect of treatment with equine chorionic gonadotrophin (eCG) on the follicular dynamics and function of crossbred cows with different circulating progesterone (P4) concentrations during synchronization of ovulation in a fixed-time artificial insemination (FTAI) protocol. To this end, 30 crossbred cows were submitted to a pre-synchronization protocol to ensure that all of them presented corpus luteum (CL) at the beginning of the protocol, and were evaluated by transrectal ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…Studies indicate that the administration of eCG in the protocol increases follicular growth rate since it improves the ovarian follicular development due to follicle-stimulating hormone and luteinizing hormone-like activity [21]. In this context, the present study suggests that all treatments were affected by eCG since the follicular growth rate observed is similar to those reported by other authors, who observed rates ranging from 1.3 to 1.8 mm/day in B. t. taurus using ovulation synchronization protocols [22,23]. Growth rates ranging from 0.7 to 1.8 mm/day in crossbred cows have also been found by other authors [24].…”
Section: Discussionsupporting
confidence: 89%
“…Studies indicate that the administration of eCG in the protocol increases follicular growth rate since it improves the ovarian follicular development due to follicle-stimulating hormone and luteinizing hormone-like activity [21]. In this context, the present study suggests that all treatments were affected by eCG since the follicular growth rate observed is similar to those reported by other authors, who observed rates ranging from 1.3 to 1.8 mm/day in B. t. taurus using ovulation synchronization protocols [22,23]. Growth rates ranging from 0.7 to 1.8 mm/day in crossbred cows have also been found by other authors [24].…”
Section: Discussionsupporting
confidence: 89%
“…In this context, the FTAI protocols are very useful, and are frequently performed in acyclic cows during the postpartum period, a condition in which the cow has a low LH support and reduced follicular development (Meneghetti et al, 2009;Roche, Crowe, & Boland, 1992). Thus, the administration of Equine Chorionic Gonadotropin (eCG) is an alternative that can be used in hormonal protocols, as it has an activity similar to FSH and LH in ruminants, promoting follicular growth and oocyte maturation (Ferraz et al, 2019;Thedy et al, 2018). In the present study, the 350 IU eCG administration at the moment of the P4 device removal, may have positively influenced the cows' pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…Con la retirada del dispositivo de progesterona intravaginal en los protocolos IATF, es posible inducir un aumento en las frecuencias de los pulsos de la hormona luteinizante (LH) suficiente para el crecimiento final de los folículos dominantes, para estimular el comportamiento del estro y la ovulación (14), un factor que puede explicar por qué los resultados de las tasas de embarazo no difieren entre los tratamientos en el presente estudio.…”
Section: Discussionunclassified